Evaluation of the prescription, administration and monitoring of vancomycin in adult patients admitted to a tertiary hospital - Prado, Iara Ronana Sousa; Vicentini, Carolina Aparecida de Almeida; Cardoso, Pedro Andriolo; Carneiro, Mayara Vidal; Chiarotti, Amanda de Moraes Mamede; Souza, Vinicius Bonafé de; Ponce, Daniela; Zamoner, Welder (Seven Editora, 2024)
Introduction: Vancomycin is a strategic antibiotic in the treatment of infections caused by gram-positive bacteria. Controversies regarding its dosage and monitoring are important due to the risk of nephrotoxicity and the insurgency of resistant strains. Objectives: To describe vancomycin prescription patterns for adult patients, to observe vancomycin administration, vancocinemia collection and the timing of subsequent vancomycin dose adjustment, and to evaluate the conformity between prescription, administration and monitoring of vancomycin in a University Hospital (HU). Methodology: This was a  cross-sectional and prospective study that included adult patients admitted to four clinical and surgical wards and two wards of the intensive care unit (SETI) using vancomycin. Six visits were made to the Internal Medicine, Neurology and Orthopedics wards and five visits to the Vascular Surgery and SETI wards, in which 67 patients and 989 prescriptions were evaluated, data from medical records were collected and nursing and medical routines regarding vancomycin administration, vancocinemia collection and antibiotic adjustment were observed. Results: There was no difference between the units in terms of gender, baseline creatinine levels, length of hospital stay, days of vancomycin use, and weight, with a predominance of younger patients in Neurology and a higher mean age in Vascular Surgery. The loading dose was prescribed in 83.8% of the patients, while dilution and infusion time were prescribed, respectively, in 768 (77.6%) and 212 (21.4%) of the prescriptions. The SETIs had rates of adequacy of the loading dose and frequency of dilution prescription and infusion time statistically higher than those of the wards (p 0.02, p 0.04 and p